Cointegration test for the long-run economic relationships of East Africa community: Evidence from a meta-analysis - Yussuf Charles Yussuf (Asian Journal of Economics and Banking (AJEB), 2022)
Purpose - The purpose of the paper is to test and analyze the equilibrium economic relationships of the East Africa Community (EAC). Design/methodology/approach To attain the study's purpose the authors applied the Johansen cointegration test, including long-run structural modeling (LRSM), vector-error-correlation-model (VECM) and variance-decomposition (VDC). Findings - At I(1), both Philips-Peron (PP) and Kwiatkowski-Phillips-Schmidt-Shin (KPSS) tests show that the East Africa member states' economies are cointegrated. The result was further substantiated by the tests based on Johansen cointegration and VECM procedures, showing significant long-run and short-run economic relations. The result further reveals that despite some uncommon issues among member states such as Tanzania and Kenya, however, their economic relationships remain significant though it is negative. Moreover, the finding revealed positive and significant short-run economic relationships between Kenya, Burundi and Rwanda. Originality/value - The paper applies the cointegration techniques in the context of EAC. The result is likely to be adding value to the policymaker and also to the existing literature on the subject. This may trigger policy implications and open new research direction within the region and out.
Keywords: E00; E01; F63; 330; Economic integration; East Africa community; Johansen cointegration test; Long-run economic relationships; LRSM; VECM